Measurement of pressure dependent variations in local pulse wave velocity within a cardiac cycle from forward travelling pulse waves - Rahul Manoj; Kiran V. Raj; P. M. Nabeel; Mohanasankar Sivaprakasam; Jayaraj Joseph (Scientific Reports)
Abstract The local pulse wave velocity (PWV) from large elastic arteries and its pressure-dependent changes within a cardiac cycle are potential biomarkers for cardiovascular risk stratification. However, pulse wave reflections can impair the accuracy of local PWV measurements. We propose a method to measure pressure-dependent variations in local PWV while minimizing the influence of pulse wave reflections. The PWV is computed from the pulse transit time between two forward-traveling pulse waveforms obtained across known path length, after measured/modelled flow-based wave separation analysis (WSA). An in-vivo study of 60 participants (24 female), was conducted to compare inter- and intra-cycle variations in PWV obtained from measured and forward pulse waves. For this, proximal and distal diameter waveforms from the carotid artery, along with carotid tonometry, were recorded using a custom bi-modal arterial probe. The carotid blood flow for WSA was captured with an ultrasound imaging system. The reference PWV was derived from the Bramwell-Hill equation. After WSA, the reliability of PWV measurement improved with coefficient of variation reducing from 25% to 10% near the peak of the pulse waves and matched the reference PWV with no statistically significant difference. The average PWV at foot of the pulse wave before and after WSA were comparable to the reference PWV with no statistically significant difference. The coherence of carotid pulse pressure obtained from the mean values of PWV within a cardiac cycle after WSA with that of the carotid pulse pressure from tonometry, substantiates the results obtained for reflection-free PWV. The reliability of measuring local PWV and its pressure dependent variations within a cardiac cycle is improved by combining transit-time approach with WSA.